STATUS RETINOL, KAROTENOID DAN TOKOFEROL PEMAKAI KONTRASEPSI IMPLAN DAN SUNTIKAN DENGAN KOMPLIKASI PENDARAHAN - Tita Miawati; Yuniar R. Purwono; Susilowati Herman (Persagi, 1999)
The case study of Status of Retinol Carotenoid and Tocopherol of Implant and Injection Contraseptive Users with Bleeding Complication conducted in 3 health centers in Bogor. The total number of the subjects were 68 women who used implant contraseptive (39 were as control and 29 were as cases) and 59 women who used injection (31 were as control and 28 were as cases). The results showed were as that prevalence of anemia were 25% in injection case and 27.6% in implant case. The average of serum retinol, carotenoids and tocopherol were not significantly different between injection case and control. While the implant users were significantly different between case and control in term of serum alfa tocopherol (19.3 + 3.1 vs 13.7 + 3.04). The odd ratio for injection contraseptive ussers was 1.55 for lutein; while for implant contraseptive users was 2.49 for alfa carotene, 5.89 for alfa tocopherol and 1.39 for gamma tocopherol.Keywords: retinol, carotenooids, tocopherol, contraseptive users